Repurposing Heparin as Antimalarial: Evaluation of Multiple Modifications Toward In Vivo Application - Elena Lantero; Carlos Raúl Aláez-Versón; Pilar Romero; Teresa Sierra; Xavier Fernàndez-Busquets (MDPI AG, 2020)
Heparin is a promising antimalarial drug due to its activity in inhibiting Plasmodium invasion of red blood cells and to the lack of resistance evolution by the parasite against it, but its potent anticoagulant activity is preventing the advance of heparin along the clinical pipeline. We have determined, in in vitro Plasmodium falciparum cultures, the antimalarial activity of heparin-derived structures of different origins and sizes, to obtain formulations having a good balance of in vitro safety (neither cytotoxic nor hemolytic), low anticoagulant activity (≤23 IU/mL according to activated partial thromboplastin time assays), and not too low antimalarial activity (IC50 at least around 100 µg/mL). This led to the selection of five chemically modified heparins according to the parameters explored, i.e., chain length, sulfation degree and position, and glycol-split, and whose in vivo toxicity indicated their safety for mice up to an intravenous dose of 320 mg/kg. The in vivo antimalarial activity of the selected formulations was poor as a consequence of their short blood half-life. The covalent crosslinking of heparin onto the surface of polyethylene glycol-containing liposomes did not affect its antimalarial activity in vitro and provided higher initial plasma concentrations, although it did not increase mean circulation time. Finding a suitable nanocarrier to impart long blood residence times to the modified heparins described here will be the next step toward new heparin-based antimalarial strategies.